Analisis Data Sistem Informasi Monitoring Marketing; Tools Pengambilan Keputusan Strategic - Neng Susi Susilawati Sugiana; Bertha Musty (STMIK Banjarbaru, 2023)
A good marketing strategy must be supported by the convenience of information technology to obtain accurate and real-time information. In today's digital era, an effective and efficient marketing monitoring information system can make a major contribution in supporting marketing activities. With a good monitoring information system, marketing decision-making can be more targeted because it is based on accurate and real-time data. Using this qualitative analysis method and clustering, as well as looking at various consumer behavior factors whose insensitivity often occurs can be categorized as opportunities that can influence strategic decision making in making decisions that are more precise and accurate. So that the results of this data analysis can become a forecast for the development of a marketing strategy or a historical dictionary that is appropriate for various business owners to have as an important aspect to help business owners make the right decisions and develop their business in the future in the form of technological aspects packaged as a dictionary. marketing history.Keywords: Data Analysis; Monitoring Information System; marketing; Decision-making; strategic AbstrakStrategi pemasaran yang baik harus didukung oleh kemudahan teknologi informasi untuk dapat memperoleh informasi yang akurat dan real-time. Dalam era digital seperti sekarang, sistem informasi monitoring marketing yang efektif dan efisien dapat memberikan kontribusi besar dalam menunjang kegiatan marketing. Dengan adanya sistem informasi monitoring yang baik, pengambilan keputusan pemasaran dapat menjadi lebih tepat sasaran karena berdasarkan data yang akurat dan real-time. Menggunakan metode analisis kualitatif ini dan menclusterkan, serta melihat berbagai faktor perilaku konsumen yang insensitas munculnya sering terjadi dapat dikategorikan sebagai peluang yang dapat memengaruhi pengambilan keputusan strategic dalam pengambilan keputusan yang lebih tepat dan akurat. Sehingga hasil Analisa data ini dapat menjadi sebuah peramalan untuk pengembangan strategi marketing atau sebuah kamus historical yang layak dimiliki oleh berbagai pemilik bisnis sebagai aspek penting untuk membantu pemilik bisnis membuat keputusan yang tepat dan mengembangkan bisnis mereka di masa depan dalam bentuk aspek teknologi yang dikemas sebagai kamus historical pemasaran.